Optimal software-defined network topology for distributed denial of service attack mitigation - Branislav Mladenov; Georgi Iliev (Bulletin of Electrical Engineering and Informatics, 2020)
Distributed denial of service (DDoS) attacks are a major threat to all internet services. The main goal is to disrupt normal traffic and overwhelms the target. Software-defined networking (SDN) is a new type of network architecture where control and data plane are separated. A successful attack may block the SDN controller which may stop processing the new request and will lead to a total disruption of the whole network. The main goal of this paper is to find the optimal network topology and size which can handle Distributed denial of service attack without management channel bandwidth exhaustion or run out of SDN controller CPU and memory. Through simulations, it is shown that mesh topologies with more connections between switches are more resistant to DDoS attacks than liner type network topologies.